The Effectiveness of Cold Atmospheric Plasma (CAP) on Bacterial Reduction in Dental Implants: A Systematic Review - Ahmed Yaseen Alqutaibi; Abdulbari Aljohani; Abdullah Alduri; Abdulmajid Masoudi; Anas M. Alsaedi; Hesham Mohammed Al-Sharani; Ahmed E. Farghal; Ahmad Abdulkareem Alnazzawi; Afaf Noman Aboalrejal; Abdel-Aleam H. Mohamed; Muhammad Sohail Zafar (Biomolecules, 2023)
Background: The emergence of dental implants has revolutionized the management of tooth loss. However, the placement of clinical implants exposes them to complex oral environment and numerous microscopic entities, such as bacteria. Cold atmospheric plasma (CAP) is often used to treat the surfaces of dental implants, which alters morphological features and effectively reduces bacterial load. Purpose: This systematic review aims to assess the existing literature on the bactericidal properties of CAP when used on various kinds of dental implant surfaces. Review Method: An in-depth examination of MEDLINE/PubMed and EMBASE was performed to identify relevant studies, with the most recent search conducted in May 2023. Studies were selected based on their exploration of CAP’s effects on dental implants compared to control groups, focusing on CAP’s bactericidal efficacy. However, studies that lacked a control group or that failed to measure bactericidal effects were excluded. Results: After applying the selection criteria, 15 studies were ultimately included in the systematic review. The collected data suggest that CAP can effectively reduce bacterial loads on dental implant surfaces, including pathogens like Streptococcus mitis and Staphylococcus aureus. Furthermore, CAP appears to combat biofilms and plaques that are key contributors to periimplantitis. Conclusion: CAP emerges as a promising treatment option, exhibiting significant bactericidal activity on dental implant surfaces. CAP can decrease the rates of bacterial biofilm and plaque formation, leading to improved outcomes for dental implant patients.